Unveiling hidden knowledge: discovering the hygiene needs of perimenopausal women. Issue 2 (April 2019) - Bhakta, Amita; Fisher, Julie; Reed, Brian
Abstract : The provision of adequate water, sanitation and hygiene (WASH) services to ensure good health and wellbeing for all is incorporated into the Sustainable Development Goals, with the aim to 'leave no-one behind'. The WASH needs of perimenopausal (PM) women are largely absent from academic literature. These personal needs are hidden knowledge. However, this article demonstrates the use of participative methodologies to 'unveil' these. A UK-based phenomenological review set the research agenda using PM women's narratives; this was later developed in urban Ghana using oral history interviews, participatory mapping and PhotoVoice. Allowing for some adaption of these tools to account for local taboos in the global South, issues were revealed that are invisible to many but still warrant attention. Moving beyond theoretical discourse, practical approaches identified infrastructural issues and ensured the inclusion of PM experience. Unveiling hidden knowledge in this way has wider implications for other issues in development agendas.